2014
DOI: 10.1073/pnas.1318945111
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput sequencing reveals inbreeding depression in a natural population

Abstract: Proxy measures of genome-wide heterozygosity based on approximately 10 microsatellites have been used to uncover heterozygosity fitness correlations (HFCs) for a wealth of important fitness traits in natural populations. However, effect sizes are typically very small and the underlying mechanisms remain contentious, as a handful of markers usually provides little power to detect inbreeding. We therefore used restriction site associated DNA (RAD) sequencing to accurately estimate genome-wide heterozygosity, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
243
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 234 publications
(265 citation statements)
references
References 46 publications
(60 reference statements)
16
243
4
Order By: Relevance
“…Our results are consistent with two recent studies that used different approaches to evaluate the precision of marker-versus pedigree-based measures of individual inbreeding when using thousands of SNPs. Hoffman et al (2014) found a moderately high correlation between heterozygosity estimated at 413 000 SNPs and F P (r 2 = 0.74) in oldfield mice (Peromyscus polionotus). However, the predicted r 2 between heterozygosity and IBD G (based on estimated identity disequilibrium in their oldfield mice) was ≈1; thus, IBD G was likely more precisely predicted by heterozygosity than by F P in their study population.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Our results are consistent with two recent studies that used different approaches to evaluate the precision of marker-versus pedigree-based measures of individual inbreeding when using thousands of SNPs. Hoffman et al (2014) found a moderately high correlation between heterozygosity estimated at 413 000 SNPs and F P (r 2 = 0.74) in oldfield mice (Peromyscus polionotus). However, the predicted r 2 between heterozygosity and IBD G (based on estimated identity disequilibrium in their oldfield mice) was ≈1; thus, IBD G was likely more precisely predicted by heterozygosity than by F P in their study population.…”
Section: Discussionmentioning
confidence: 96%
“…Physical genome maps are currently available for few taxa (Ellegren, 2014). Therefore, our results are encouraging for studies on organisms lacking genome maps and have no choice but to measure individual inbreeding with unmapped loci (for example, Hoffman et al, 2014).…”
Section: How Many Snps Are Needed?mentioning
confidence: 87%
See 2 more Smart Citations
“…We suggest that it is generally advantageous to use molecular markers in heterozygosity-fitness studies, especially if (1) large numbers (⩾10 000) of SNPs can be genotyped (see, for example, Hoffman et al, 2014;Kardos et al, 2015;Huisman et al, 2016;Wang, 2016), (2) if moderate numbers (∼30-100) of microsatellites can be genotyped and (3) the pedigree covers only few generations or pedigree founders are related.…”
Section: Discussionmentioning
confidence: 99%